Moodle-Based E-learning Development by Implementing Gamification Concept - Landebila, Jumiatin; Saputra, Hendra Nelva; Razilu, Zila (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This research aims to produce moodle-based e-learning media by applying the concept of gamification to the subject "Visual Communication Design in Industry 4.0", targeting class X students at SMK Negeri 5 Kendari. This research uses the R & D (Research and Development) method by applying the ADDIE model research procedure (Analysis, Design, Development, Implementation, Evaluation). The type of data used in this research is quantitative data derived from primary data. The data obtained in this study came from the results of public tests which included media experts, material experts, and field tests conducted by students. The data generated was then analysed using descriptive techniques to test the feasibility of the media. The results of the feasibility test conducted by three media experts stated "Very Feasible" with an average percentage of 93.89%, the results of the feasibility test conducted by three material experts stated "Very Feasible" with an average percentage of 97.08%, and also the results of the feasibility test conducted by students stated "Very Feasible" with an average percentage of 87.97% so that the gamification-based e-learning media developed is very feasible to use as learning media.